Modulation of Ground Deformation and Earthquakes by Rainfall at Vesuvius and Campi Flegrei (Italy) - Petrosino, Simona; Ricco, Ciro; Aquino, Ida (Frontiers in Earth Science, 2021)
In the present paper, we analyse ground tilt, seismicity rates and rainfall amount recorded over 6 years (2015-2021) at Vesuvius and Campi Flegrei, two volcanic areas located in the south of Italy. The results indicate that at both the volcanoes the ground deformation reflects the seasonal pattern of the hydrological cycles. On the other hand, a correlation analysis on shorter time scales (days) shows that at Vesuvius rain and ground tilt are poorly correlated, while rain and earthquakes are almost uncorrelated. Instead, at Campi Flegrei precipitations can affect not only ground deformation but also earthquake rate, through the combined action of water loading and diffusion processes in the medium. Our observations suggest that rain-induced hydrological variations play a role in modulating the dynamics of those volcanic systems, like Campi Flegrei, which are close to a metastable or critical state.